I survived the joplin tornado, 2011 eaudiobook - Tarshis, Lauren (I Survived, 2017)
A destructive force is about to hit the city of Joplin... Eleven-year-old Dexter has always wanted to see a tornado. So when he gets the incredible opportunity to go storm chasing with the famous Dr. Norman Rays, he has to say yes! Dr. Rays is the host of Tornado Mysteries, the show that Dex and his older brother, Jeremy, watched every night until Jeremy joined the U.S. Navy SEALs and left Joplin. Dex certainly knows how deadly tornadoes can be, but this one isn't heading toward Joplin, and wouldn't it be great to have a brave and exciting story of his own to tell Jeremy when he comes home? But when the tornado shifts direction, Dexter's bravery is about to get seriously tested...